„Romeo i Julia” Piotra Czajkowskiego. W 400-lecie śmierci Wiliama Szekspira - Grajewski, Czesław (Saeculum Christianum. Pismo Historyczne, 2018)
With the biography of P. Tchaikovsky in the background, the author describes the circumstances of the creation of the overture Romeo and Juliet. Then he briefly analyzes the composition itself and describes its character.